The impact of research and development on total factor productivity in South Africa: an application of autoregressive distributed lag model approach. (2018) - Sekaiwa, Tshepo; Maredza, Andrew
This study analyses the impact of research and development (R&D) on total factor productivity (TFP) in South Africa from 1970 to 2013. The study tests the Schumpeterian theory of growth which suggests that TFP growth results from interalia R&D. The study uses autoregressive distributed lag (ARDL) procedure to study TFP impact of R&D investment in South Africa. To take into account the changing structure of South African economy, the entire sample (1970-2013) and two sub-samples: 1970-1994 and 1990-2013 capturing resource-based and knowledge-based South Africa respectively are estimated. The ARDL test results revealed that cointegration exists between TFP and R&D for all the samples; implying that domestic and foreign R&D played a positive role on TFP growth of South Africa. Based on the results, the South African policy makers are encouraged to use policy instruments to improve R&D investment, particularly domestic R&D to achieve higher TFP growth.